FARMERS’ HOUSEHOLD SAVINGS COMPARED TO SELECTED HOUSEHOLDS GROUPS - Aleksander Grzelak (Annals of the Polish Association of Agricultural and Agribusiness Economists)
The aim of the article is to diagnose the dynamics of household savings among farmers in Poland in comparison to other social groups of households. The study attempts to relate empirical findings to selected income theories. Data from the household budgets of the Central Statistical Office (GUS) were used in this analysis. It was found that the existing theories do not correspond to the savings behaviors of farming households. It can be stated that only the integration of the permanent income theory, Modigliani and Brumberg’s life-cycle hypothesis, and the relative income theory would provide an interesting alternative. Savings in farming households increased and were generally higher in the analysed years compared to households overall and wage-earning households, despite lower income levels. However, the income levels were generally lower, which means that the propensity to save is relatively high among farming households. Farming households differ from households overall and wage-earning households in that part of the accumulated savings is allocated to financing investments or current expenses in the farm. As a result, this motivates the heads of these households to save, given the widespread aversion to increasing risk associated with using external sources of financing (credits).